S109 Effect of continued treatment with pirfenidone following a clinically meaningful decline in percent predicted forced vital capacity in patients with idiopathic pulmonary fibrosis (IPF). (12th November 2015) - Noble, PW; Albera, C; Bradford, WZ; Costabel, U; Glaspole, I; Glassberg, MK; Lancaster, L; Lederer, DJ; Lin, Z; Pereira, CA; Swigris, JJ; Valeyre, D; et al.
Abstract : Introduction and objectives: The clinical course in patients with IPF is characterised by substantial inter- and intra-subject variability in the rates of disease progression, thereby confounding clinical assessments of therapeutic responses in individual patients. We pooled data from three Phase 3 trials to assess the potential benefit of continued treatment with pirfenidone in patients who experienced a ≥10% decline in percent predicted forced vital capacity (%FVC) during the first 6 months of treatment. Methods: Source data included all patients randomised to treatment with pirfenidone 2403 mg/d or placebo in the Phase 3 ASCEND or CAPACITY studies (N = 1247). We selected patients with a ≥10% absolute decline in%FVC by the month 3 or 6 study visit and compared the proportion of patients in the pirfenidone and placebo groups who experienced any of the following during the subsequent 6-month interval: (1) ≥10% absolute decline in%FVC or death; (2) no further decline in%FVC; or (3) death. Observed data were used in the analysis. Results: 34 (5.5%) and 68 (10.9%) patients in the pooled pirfenidone and placebo groups, respectively, experienced a ≥10% absolute decline in%FVC between baseline and month 6 (relative difference, 49.5%). Analysis of outcomes during the subsequent 6-month interval demonstrated that fewer patients in the pirfenidone group compared with placebo experienced a ≥10% decline in%FVC or death (pirfenidone, 2/34 [5.9%] vs. placebo, 19/68 [27.9%]). More patients in the pirfenidone group compared with placebo had no further decline in%FVC (20/34 [58.8%] vs. 26/68 [38.2%]; Table 1 ). Additionally, there were fewer deaths in the pirfenidone group (1/34 [2.9%]) compared with placebo (14/68 [20.6%]). Conclusions: Among patients who experienced a ≥10% decline in%FVC during the first 6 months of treatment, continued treatment with pirfenidone resulted in a lower risk of%FVC decline or death during the subsequent 6 months. These findings suggest a potential benefit to continued treatment with pirfenidone despite an initial decline in FVC.